The male and female complete mitochondrial genome sequences of the Endangered freshwater mussel Potomida littoralis (Cuvier, 1798) (Bivalvia: Unionidae). (2nd September 2016) - Froufe, Elsa; Gan, Han Ming; Lee, Yin Peng; Carneiro, João; Varandas, Simone; Teixeira, Amílcar; Zieritz, Alexandra; Sousa, Ronaldo; Lopes-Lima, Manuel
Abstract: Freshwater mussels of the family Unionidae exhibit a particular form of mitochondria inheritance called double uniparental inheritance (DUI), in which the mitochondria are inherited by both male and female parents. The (M)ale and (F)emale mitogenomes are highly divergent within species. In the present study, we determine and describe the complete M and F mitogenomes of the Endangered freshwater mussel Potomida littoralis (Cuvier, 1798). The complete M and F mitogenomes sequences are 16 451 bp and 15 787 bp in length, respectively. Both F and M have the same gene content: 13 protein-coding genes (PCGs), 22 transfer RNA (trn) and 2 ribosomal RNA (rrn) genes. Bayesian analyses based on the concatenated nucleotide sequences of 12 PCGs and 2 rrn genes of both genomes, including mitogenome sequences available from related species, were performed. Male and Female lineages are monophyletic within the family, but reveal distinct phylogenetic relationships.